2014
DOI: 10.1098/rspb.2013.2310
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genomic plasticity of alternative male reproductive tactics in sailfin mollies

Abstract: A major goal of modern evolutionary biology is to understand the causes and consequences of phenotypic plasticity, the ability of a single genotype to produce multiple phenotypes in response to variable environments. While ecological and quantitative genetic studies have evaluated models of the evolution of adaptive plasticity, some long-standing questions about plasticity require more mechanistic approaches. Here, we address two of those questions: does plasticity facilitate adaptive evolution? And do physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 66 publications
2
55
1
Order By: Relevance
“…The most remarkable example is satellite behaviour, in which parasitic males do not perform courtship by themselves but instead intercept females courted by other males (e.g. guppy [10][11][12] and frog [13]). In this example, parasitic males exploit the investment by other males [2].…”
Section: Introductionmentioning
confidence: 99%
“…The most remarkable example is satellite behaviour, in which parasitic males do not perform courtship by themselves but instead intercept females courted by other males (e.g. guppy [10][11][12] and frog [13]). In this example, parasitic males exploit the investment by other males [2].…”
Section: Introductionmentioning
confidence: 99%
“…Where microarrays suffer strain-or speciesspecific probe biases, RNA-seq permits studying the evolutionary forces shaping gene expression at the whole-transcriptome level (Busby et al 2011;Romero et al 2012). In ecological contexts, RNA-seq enables the examination of expression differences underlying interindividual or interpopulation variation in ecologically important traits such as disease resistance (Bonneaud et al 2011) and mating behaviour (Fraser et al 2014;Schunter et al 2014), and the identification of genes of potential adaptive significance in changing environments (Meyer et al 2011;Smith et al 2013;Veilleux et al 2015). RNA-seq is a key technology facilitating the recent push towards using integrative biology to understand molecular mechanisms of phenotypic and behavioural plasticity in wild populations (AubinHorth & Renn 2009;Harris & Hofmann 2014).…”
mentioning
confidence: 99%
“…The appeal of measuring genome-wide expression, as opposed to focusing on fixed genetic variation, is that it can reveal which genes in the genome are responsive to the environment, and therefore likely to be related to phenotypic plasticity. For example, recent genome-wide transcription studies have revealed that roughly ~10% of all of the genes in the genome are differentially expressed in response to a mating opportunity [2429], predation risk [7,30,31], or a territorial challenge [6,32,33]. Recent evidence suggests that transcriptional responses can be the result of a conserved genomic response to social challenges [34].…”
Section: The Problem: How To Incorporate Molecular Mechanisms?mentioning
confidence: 99%
“…Genome-wide gene expression studies have also detected differences in brain gene expression between behavioral types, e.g. scouts vs nonscout honey bees [35] and alternative mating types [29,36,37]. A few particularly exciting recent studies have both compared gene expression between behavioral types and changes in gene expression in response to the environment [29,38].…”
Section: The Problem: How To Incorporate Molecular Mechanisms?mentioning
confidence: 99%
See 1 more Smart Citation